2003
DOI: 10.1097/01.ju.0000091644.41330.2a
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Specific Antigen Bounce After Simultaneous Irradiation for Prostate Cancer: The Relationship to Patient Age

Abstract: Young men with prostate cancer treated with brachytherapy have a significantly higher frequency, earlier onset and longer duration of PSA bounce than older men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 7 publications
6
25
0
Order By: Relevance
“…9,11,14,15 The observation of a slight bounce in PSA in 3 of 31 patients that was resolving by the time TRT was initiated in the current series reinforces the approach of delaying TRT to !18 months after implantation, so that the bounce phenomenon is not interpreted as secondary to TRT.…”
Section: Discussionmentioning
confidence: 89%
“…9,11,14,15 The observation of a slight bounce in PSA in 3 of 31 patients that was resolving by the time TRT was initiated in the current series reinforces the approach of delaying TRT to !18 months after implantation, so that the bounce phenomenon is not interpreted as secondary to TRT.…”
Section: Discussionmentioning
confidence: 89%
“…Prior studies used different isotopes and administered EBRT with or without brachytherapy. 4,5,8,9,18,19 PSA bounce is a common phenomenon after brachytherapy. PSA bounce has previously been defi ned as an increase of more than 0.1 ng/ml, 3,5,8,9,12 followed by a subsequent decrease to less than that level; as an increase of more than 0.2 ng/ml, 2,3,6,7,11 followed by a decline or a minimal rise of 0.4 ng/ml 3,5,12 during a 3-6 month period, followed by a drop of any magnitude; or as a more than 35% elevation 5,12 in PSA compared with the most recent value, followed by a decline to a level at or less than the prebounce value.…”
Section: Discussionmentioning
confidence: 99%
“…2 Approximately 15%-60% of hormone-naive patients show a temporary PSA elevation after brachytherapy. [2][3][4][5][6][7][8][9][10][11][12] It has been proposed that this PSA "bounce" is probably the result of some mechanism compromising membrane integrity; that is, radiation-induced prostatitis, in PSA-producing epithelium. In 1997, the American Society for Therapeutic Radiology and Oncology (ASTRO) consensus conference recommended three consecutive increases in PSA levels after the nadir, with readings spaced 3-6 months apart, as the defi nition of biochemical failure.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies (Todor et al, 2011;Guarneri et al, 2013) have reported that age is an important factor that may influence whether benign rebound occurs, and that the younger the patient the more likely that postoperative blood PSA will show benign rebound. Critz et al (2003) found that the incidence of benign rebound in patients ≤60 years is twice that of those ≥71 years (57 vs 26%; P < 0.0001). Thompson et al (2010) found that 60% of PSA-positive rebound occurred in patients <59 years.…”
Section: Ultrasound-guided [mentioning
confidence: 96%